TAQUINIDOS DE AYSEN (XI REGION) Y MAGALLANES (XII REGION) CHILE (DIPTERA: TACHINIDAE) - Cortés P., Raúl (Acta Entomológica Chilena, 2022)
The World’s Southernmost parasitic species of Tachinid flies (Díptera) referred to in this paper come from the austral territories of Aysen (XI Región) and Magallanes (XII Región) in South Chile, compri- sing the large area covered by degrees 44 to 56 of Latitude South. The genera and species dealt with herein will certainly occur as well in the adjacent territory of South Argentina. The species reported from the Islands of Tierra del Fuego, Navarino, Deceit, Wollaston and Picton are indeed the extremely Southern in the Neotropical Región and in the world. 51 genera and 71 species are recorded in this paper of which Comopsis (Cuphocerini), Notoderus (Lyphiini), Periostoma (Leucostomatini) and Telonotomyia (Aphriini) are new monotypic genera, while Clastoneuriopsis Reinhard 1939 is a new genus for Chile and So. America. Admontia finisterrae, Ateloglutus lanfrancoi, Clastoneuriopsis magallanica and Coscaronia antennalis are described as new species. Trichoprosopus Macquart 1843 and Trichoceronia Cortés 1946 up to now in the Tribe Trichoprosopini of the Proseninae are transferred in this paper to the Sub-family Tachininae according to male genitalia evidence, and thus the whole Tribe Trichoprosoni is ranked in a new status as a true Tachininae. Most of the species are parasitic on larvae of Scarabs (Col.) and of Hepialids (Lep.) suggesting transantarctic biogeographic relations with “sister groups” in New Zealand also parasitic on equivalent hosts, thus corresponding to what Dr. C.H.T. Townsend calis the “Antarctic contingent”.